Kantian consequentialism - Cummiskey, David; Oxford eBooks (New York ; Oxford : Oxford University Press, 1996)
This title attempts to derive a strong consequentialist moral theory from Kantian foundations. It thus challenges the prevailing view that Kant's moral theory is hostile to consequentialism, and brings together the two main opposing tendencies in modern moral theory.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Kant, Immanuel, -- 1724-1804 -- Ethics; Consequentialism (Ethics); Electronic books